On-the-ground perspectives of women's land rights in Uganda. Issue 6 (18th August 2018) - Kabahinda, Jackline
ABSTRACT: This article explores the significance and application of human rights in a local context, investigating the meaning and operationalisation of human rights on the ground. It focuses on the reality of women's land rights in rural Uganda, when juxtaposed with international human rights instruments: the Universal Declaration of Human Rights (UDHR) and its implementing covenants, the International Convention on Economic Social Cultural Rights (ICESCR), International Convention on Civil Rights (ICCR), and the Convention on All Forms of Discrimination Against Women (CEDAW).